A post-mortem computed tomography imaging method for predicting the anteroposterior and superoinferior positions of the Japanese adult eyeball in the orbit. (June 2022) - Kazuta, Mariko; Hajime, Utsuno; Makino, Yohsuke; Minegishi, Saki; Iwase, Hirotaro; Sakurada, Koichi
Highlights: We predicted the eyeball position for facial approximation in Japanese adults. The eyeball position of the Japanese was different from that of other populations. Prediction of the eyeball protrusion indicated high correlation in this study. We measured the eyeball position in Japanese adult cadaver. Abstract: Objectives: : Predicting the position of the human eyeball is particularly difficult in facial approximation. While prediction methods for eyeball position based on skull features have been proposed in Caucasians, this study aimed to establish a method using anatomical landmarks on Mongoloid skulls. Materials and Methods: : Using post-mortem computed tomography (PMCT) images, we plotted landmarks on the skull and soft tissues of 146 Japanese adult cadavers and recorded the coordinates using CT image viewer software (OSIRIX MD, Pixmeo). We measured the distances between these landmarks and processed the data statistically in Microsoft Excel®>. Results: : The results showed significant differences for many variables compared to previous guidelines and measurements, suggesting the need for a prediction method based on ancestry. We identified factors such as sex, body mass index, and age that influenced eyeball location. Next, we estimated the prediction standards of the globe position from the measurements obtained in this study and applied them to unidentified cadavers. The correlation coefficient was 0.737 in the anteroposterior direction and 0.291 in the superoinferior direction. The small correlation coefficient for eye protrusion was likely based on the lack of power, owing to the limited number of samples in the database. Conclusion: : Important factors in predicting facial features, such as sex, age, and ancestry, contributed to more accurate facial approximation. Future analyses using a larger database to establish more accurate prediction guidelines are necessary.